Development of Microbial Analysis – Faster Detection and Business Opportunities - Välimaa, Anna-Liisa; Uusitalo, Sanna; Yueqiang, Xu; Laitinen, Riitta; Hiltunen, Jussi; Koivumäki, Timo (Natural Resources Institute Finland, Luke, 2016)
Foodborne diseases represent a serious public health issue. For example in the USA it is estimated that the total economic impact is $50 to $80 billion annually in health care costs, lost productivity, and diminished quality of life (Byrd-Bredbenner et al. 2013). For this reason, food safety authorities around the world have realized the need for a strict regulatory framework, including an exhaustive food testing regime. In the European Union (EU) the Comission regulation (EC) No 2073/2005 on microbiological criteria for foodstuffs has been established for food pathogens including Listeria monocytogenes. According to the regulation the manufactures and other food business operators are responsible for the production and delivery of safe food. The follow up will be carried out by self-monitoring methods. Conventional methods are often sensitive, but extremely time-consuming. Depending on the target microorganism, it may take from several days to over two weeks to obtain a fully confirmed positive test result (Velusamy et al. 2010). In present food business this timescale is too long. Because of that Fast Microbe Analysis (FMA) solution was developed in this project. The target of microbiological part of the study was to shorten the lag phase time in L. monocytogenes enrichment procedure and determine the selectivity of growth media combined with IMS. It was clearly seen that it is really difficult to make remarkable improvements in shortening the lag phase time. The selectivity of growth media combined with immunomagnetic separation concluded that, the developed method is applicable in Listeria spp. detection, but not specific for L. monocytogenes detection. By combining surface enhanced Raman spectroscopic (SERS) detection with the sample concentration the detection limit of 104 CFU/ml was obtained. SERS was based on the hybrid nanoparticle and corrugated substrate configuration, while immunomagnetic bead separation and hydrophobic surfaces were utilized to concentrate samples. Business research in FMA project included indetification of market opportunities for developed FMA solution, identification of the food safety business ecosystem and the related possible ecosystem business model for the developed solution. Business opportunities for FMA solution in other industries were also analyzed.
FMA Fast Microbial Analysis project was funded by TEKES, decision numbers 40173/13, 40174/13 and 40175/13
Keywords: Listeria monocytogenes; nanotechnology; SERS; fast analysis; business ecosystem; analyysimenetelmät; ekosysteemit; nanotekniikka